ANALISIS YURIDIS TANGGUNG JAWAB PELAKU USAHA AKIBAT PENGARUH IKLAN YANG MENYESATKAN - j.c.h, willy vanroly; Svinarky, Irene (LPPM Universitas Putera Batam, 2021)
Business actors rarely do not know about prohibitions in advertising, but there are still business actors who commit violations related to this and there are still business actors who are incomplete in providing information so that there are many misleading advertisements circulating regarding business actors' products. In this study, it is more directed to the responsibility of business actors due to the influence of misleading advertisements. Therefore, the authors are interested in taking the title of juridical analysis of the responsibility of business actors due to the influence of misleading advertisements. The objectives described in this study are as follows; first, knowing the form of responsibility of business actors due to the influence of misleading advertising; second, knowing the efforts made by consumers in the event of a loss to the final consumer. The research method is the type of normative legal research or can also be said to be a literature study. The results of the study, the forms of accountability of business actors to final consumers include; Contractual liability, the principle of responsibility due to default; Fault liability, the principle of responsibility for errors; Criminal liability, the principle of absolute responsibility.